TOLERANSI TANAMAN KEDELAI TERHADAP CEKAMAN AIR: UJI LAPANG BEBERAPA GENOTIPE TOLERAN - Didy Sopandie; , Hamin; Muhammad Jusuf; , Supijatno (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1997)
The purpose of this field verification was to determine the stability of yield of several drought-tolerant soybean genotypes selected from green house evaluation. The plants were planted at Muneng, Probolinggo in dry season (June-September 1995) with and without irrigation. From 5 tolerant genotypes, Mlg 2999 and Mlg 3474 gave a good stability of tolerance as evidence by less significance of growth and grain yield reduction. The tolerant genotypes of Mlg 2805 and Mlg 2984 suffered from tremendous leaves and pods abcission, leading to low yield.